The Efficacy of Evidence-Based Practice Training in Enhancing Decision-Making Competency Utilizing Fishbone Diagrams Among Nurse Managers at Hospital B Bandung - Lala, Angela; Harry Susilo, Wilhelmus; Tutiany, Tutiany (Indonesian Health Journal (IHJ), 2024)
The nurse manager is crucial in overseeing and directing nursing services to accomplish organizational objectives effectively. Nurse managers must possess the skill of evidence-based decision-making. This reseacrh aims to determine the efficacy of evidence-based practice training in enhancing decision-making skills among nurse managers at Hospital B Bandung, specifically through utilizing the Fishbone Diagram. This study employs quantitative research methodologies utilizing a pre-experimental design, specifically a one-group pre-post design. The research sample comprised 62 nurse managers, including 28 section heads, deputy section heads, coordinators, and 34 CCMs. These individuals received evidence-based practice decision-making training interventions involving fishbone diagrams and post-training intervention. The data analysis method employs the Wilcoxon bivariate test and the multivariate ordinal logistic regression test. The intervention yielded statistically significant improvements in decision-making practices, knowledge, attitudes, and skills. The p-value for these changes was 0.000 (p < 0.05), indicating a high confidence level in the results. This study suggests that providing evidence-based practice training to hospital nurse managers is necessary to enhance their decision-making skills. This can be achieved by utilizing fishbone diagrams or other similar tools.